2017
DOI: 10.1038/s41598-017-02124-1
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles-Decorated Titanium Oxynitride Nanotube Arrays for Enhanced Solar Fuel Generation

Abstract: We demonstrate, for the first time, the synthesis of highly ordered titanium oxynitride nanotube arrays sensitized with Ag nanoparticles (Ag/TiON) as an attractive class of materials for visible-light-driven water splitting. The nanostructure topology of TiO2, TiON and Ag/TiON was investigated using FESEM and TEM. The X-ray photoelectron spectroscopy (XPS) and the energy dispersive X-ray spectroscopy (EDS) analyses confirm the formation of the oxynitride structure. Upon their use to split water photoelectroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 48 publications
5
21
0
Order By: Relevance
“…2 d two peaks are detected at 367.82 eV, 373.9 eV correspond to Ag 3d5/2 and Ag 3d3/2 binding energies, respectively. The splitting of the 3d doublet is 6.08 eV, indicating that Ag mainly exists in metallic state on PA6 nanofibers ( Soliman et al, 2017 ). Therefore, the XPS results confirmed that Ag metallic nanoparticles on the PA6 nanofiber.…”
Section: Resultsmentioning
confidence: 99%
“…2 d two peaks are detected at 367.82 eV, 373.9 eV correspond to Ag 3d5/2 and Ag 3d3/2 binding energies, respectively. The splitting of the 3d doublet is 6.08 eV, indicating that Ag mainly exists in metallic state on PA6 nanofibers ( Soliman et al, 2017 ). Therefore, the XPS results confirmed that Ag metallic nanoparticles on the PA6 nanofiber.…”
Section: Resultsmentioning
confidence: 99%
“…This is a good indication for nitrogen incorporation into the TiO 2 lattice. 24 While the small peak at 0.776 eV is ascribed to Co, the sharp peak appeared at 2.984 eV is characteristic of Ag. The peak appeared at 4.508 eV is characteristic of Ti.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20] Equally important is the use of localized surface plasmon resonance (LSPR) of metal nanoparticles that enables the strong coupling of visible light with charge carriers in the nanoparticles, thus facilitates the water splitting process. [21][22][23][24] On the other hand, cocatalysts have been used to improve the electrocatalytic performance of many photocatalysts used to split water. Among those cocatalysts, Co-Pi was shown to increase the conductivity of the material and decrease the water splitting reaction overpotential.…”
Section: Introductionmentioning
confidence: 99%
“…For the photodegradation of RhB under visible light irradiation, the photocatalytic efficiency of this faceted Ag 4 V 2 O 7 nanoplates was not only significantly higher than that [37]. It should be noted that commonly used crystal facet engineering techniques like using template, ionic liquids, or surfactant as structure-directing agents, to a certain extent, are limited for silver-containing photocatalysts due to the ease of reducing and forming undesired insoluble compounds of Ag + ions during the synthesis process [9,38]. Figure 6 demonstrated the recyclability testing results of RhB over the random-and c-axis-oriented Ag 4 V 2 O 7 samples for three recycling photocatalytic runs under solar light irradiation.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 93%
“…Novel ternary oxide-based photocatalysts including silver vanadates as alternatives to traditional TiO 2 have been recently attracted a lot of attention in both basic research and applications [1][2][3][4]. For these photocatalytic systems, current research activities focus on enhancing their photocatalytic performances via morphological controlling, crystal facet engineering, and reducing band gap by elemental doping separately or simultaneously [5][6][7][8][9]. The reduction in the average grain size of a photocatalyst from microto nanoscale, for instance, was confirmed to enhance the photocatalytic activity due to the increase in its surface area and light absorption [5].…”
Section: Introductionmentioning
confidence: 99%